Inclusive Governance in Nepal: Problem and Challenges (Journal of Governance and Development (JGD), 2016)
Inclusive governance(IG) though virtually encompasses to mainstream the marginalized groups into the broader framework of the governance policies, systems and practices; it is an integrated approach that equally manages to improve two parts of the service delivery - efficient delivery of service, and empowering marginalized communities to demand services. IG is not only about structural change and policy, but it also includes how the actors in governance act and interact with others. Nepal is constitutionally a federal republic democratic (as per the constitution of Nepal- 2015) though the issues on demarcation of provinces and number of local level government have not properly settled yet. A prominent characteristic of Nepal is high ethnic and cultural diversity. Population Census, 2011 has identified 126 ethnic groups, and 123 languages. Since enforcement of IG in this context is challenging, a mass of population still feel that they have not been able to harness the real fruit of IG. In this context, this paper takes references of constitution, national policies, bureaucratic representation and other issues to critically analyze the initiations and achievements in Nepal in shaping IG to real system.